CREATION OF A WEBSITE-BASED CHATBOT APPLICATION AT THE CLASS I IMMIGRATION OFFICE OF TPI EAST JAKARTA - Galuh Boy Hertantyo; W Wilonotomo; Mayza Fairda (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The customer service of the immigration office class i tpi east Jakarta is aimed to improve the service to the applicant or applicants.The applicant or applicants have to take the time to consult with customer service .In this case, the 1st class Immigration Office East Jakarta still relies on human resources as an online customer service to response questions from applicants. Given the increasing amount of applicants, it is not very effective nor efficient to answer questions one by one given that not many applicants have much time in their day to receive informations they need in such a long time, want things quickly in a very short time. This study is an attempt to develop a web based chatbot information systems application that can be used by the applicants of the 1st class Immigration Office East Jakarta so that they can obtain informations as fast as the speed of light. The Methods used for this study is the method of extreme programming. Application programming language, it uses an MySQL database and the PHP. The result of the building of the chatbot application is a result of testing of testing was definitely using black box, it can be concluded that this application can run well and answer every question quickly in accordance expected